Improving Student Learning Achievement in Islamic Education Learning by Implementing the PAKEM Learning Model at SD Negeri 7 Tangan-Tangan - Wati, Ida (Jurnal Profesi Guru Indonesia, 2025)
The success of the teaching and learning process in the classroom is largely determined by the learning strategy, no matter how complete and clear the other components are, without being implemented through the right strategy, these components will have no meaning in the process of achieving goals. Therefore, every time a teacher teaches, they are required to apply a certain strategy or method in implementing learning. This study is based on the problems: (a) How is the improvement of Islamic Religious Education learning achievement with the implementation of the PAKEM learning model? (b) How does the PAKEM learning model affect students' learning motivation? While the objectives of this study are: (a) To find out the improvement of students' learning achievement after the implementation of the learning strategy to improve thinking skills, (b) To find out the effect of students' learning motivation after the implementation of the PAKEM learning model. This study uses three rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this study is class students. The data obtained are in the form of formative test results, observation sheets for teaching and learning activities. From the analysis results, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (68.00%), cycle II (80.00%), cycle III (92.00%). The conclusion of this study is that the PAKEM learning model can have a positive effect on student learning motivation, and this learning model can be used as an alternative to PAI learning.